Colonization with extended-spectrum β-lactamase and carbapenemase-producing Enterobacterales in Ethiopia: A systematic review and meta-analysis - Mitkie Tigabie; Getu Girmay; Yalewayker Gashaw; Getachew Bitew; Abebe Birhanu; Eden Getaneh; Azanaw Amare; Muluneh Assefa (PLoS ONE, 2025)
Background The human intestinal tract contains many commensals. However, during an imbalance of the normal microbiota following exposure to antibiotics, extended-spectrum β-lactamase- and carbapenemase-producing Enterobacterales emerge. Individuals colonized with these bacteria may develop subsequent infections themselves. Therefore, this review aimed to estimate the colonization rate of extended-spectrum β-lactamase- and carbapenemase-producing Enterobacterales in Ethiopia. Methods The protocol was registered (PROSPERO ID: CRD42024550137). A systematic literature search was conducted in electronic databases, including PubMed, Google Scholar, and Hinari, to retrieve potential studies. The quality of the included studies was assessed using the Joanna Briggs Institute critical appraisal tool. The data were extracted from the eligible studies using Microsoft Excel 2019 and analyzed using STATA version 11. Heterogeneity between studies was checked using I2 test statistics. Publication bias was assessed using funnel plots and Egger’s test. A random-effects model of DerSimonian-Laird method was employed to estimate the outcomes. Results A total of 15 studies with 4713 participants were included in the meta-analysis. The overall pooled colonization rates of extended-spectrum β-lactamase-producing and carbapenemase-producing Enterobacterales in Ethiopia were 28.5% (95% CI: 16.4-40.5%, I2 =  95.9%, p <  0.001) and 4.4% (95% CI: 0.9–7.9%, I2 =  0.0%, p =  0.64), respectively. The majority of the extended-spectrum β-lactamase producers were E. coli (20.6%, 95% CI: 9.3–31.9%, I2 =  94.4%, p < 0.001), followed by Klebsiella spp. (11.1%, 95% CI: 7.7–14.6%, I2 =  20.2%, p =  0.245). Similarly, the predominant carbapenemase producers were E. coli (2.7%, 95% CI: -1.3–6.7, I2 =  0.0%, p = 0.941) and Klebsiella spp. (2.1%, 95% CI: -1.7–5.9%, I2 =  0.0%, p = 0.999). Furthermore, the pooled estimate of multidrug resistance among extended-spectrum β-lactamase producers was 71.7% (95% CI: 55.25–88.05%, I2 =  92.9%, p < 0.001). Conclusion and recommendations Approximately one-quarter of Ethiopians are colonized with ESBL-PE, while about one in 25 is colonized with CPE. These findings were obtained from studies with a moderate-to-low risk of bias. However, the results for ESBL-PE showed significant variability, indicating high heterogeneity among the studies. This colonization may lead to subsequent extraintestinal infections. Therefore, proactive action from all stakeholders is required to combat the unrecognized spread of extended-spectrum β-lactamase- and carbapenemase-producing Enterobacterales in humans.